Effects of vitamin antioxidant supplementation on cell kinetics of patients with adenomatous polyps. Issue 7 (July 1993) - Cahill, R J; O'Sullivan, K R; Mathias, P M; Beattie, S; Hamilton, H; O'Morain, C
Abstract : Colonic crypt cell proliferation is used as an indicator of risk of colorectal carcinoma. Subjects with adenomatous polyps and cancer have an increased cell proliferation and a shift of the proliferative zone towards the apex of the crypt. Epidemiological and in vitro studies have confirmed a link between vitamins A, E, C, beta-carotene, and colorectal cancer. In vitro bromodeoxyuridine immunohistochemical technique was used to assess the effect of daily oral supplementation with vitamin E (160 mg), vitamin C (750 mg), or beta-carotene (9 mg) on the colonic crypt cell proliferation in patients with adenomatous polyps (n = 40) compared with normal subjects with no colonic disease (n = 20). The patients were given supplementation for one month and colonic biopsy specimens were taken before and at the end of the trial. Patients with adenomatous polyps had a significantly higher mean labelling index per cent than controls (p < 0.001). Vitamin C or beta-carotene supplementation, however, significantly reduced the total proliferation (p < 0.005) whereas vitamin E supplementation had no effect on the colonic crypt cell proliferation. beta-carotene reduced cell proliferation at the base of the crypt only. Vitamin C reduced cell proliferation in all the crypt compartments from the apex to the base to those values seen in age and sex matched controls. These findings indicate that prolonged supplementation with vitamin C may reduce the recurrence of adenomatous polyps.